(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This article explores the significance of geometric forms in architecture, their application in composition, and methods to achieve harmony and dynamism through their arrangement. By analyzing historical and contemporary examples, this study highlights how geometric abstraction continues to influence architectural thought and practice, demonstrating the enduring relevance of these fundamental shapes in contemporary design.